Bacterial profiling, sensitivity and resistance pattern of neonatal sepsis in neonatal intensive care unit of tertiary care hospital - Srivastav, Shaunak; Verma, Manisha; Mitra, Shaila; Dwivedi, Gaurav (International Journal of Contemporary Pediatrics, 2024)
Background: This study aimed to identify the distribution of pathogens and their antimicrobial resistance patterns in the neonates admitted to the NICU of a tertiary care hospital in northern India. Methods: After obtaining written informed consent, neonates with confirmed or suspected cases of neonatal sepsis (n=167) aged 0-28 days were included. As soon as the baby arrived, all the clothes were removed and kept in a pre-heated warmer. Before administering I/V antibiotics, all the routine and culture samples were taken. The clinical data were collected and analysed using SPSS. Results: Most of the neonates were from lower middle class, out-born, LSCS, early preterm, and low birth weight (LBW). 167 neonates had culture-confirmed infections [blood culture positive (13.8%) and sepsis screen positive (86.2%)]. Gastric aspirate cytology was positive in 61.7% of patients. Maximum cytology-positive cases were seen in neonates with EOS. The most common risk factors were birth asphyxia. 142 individuals were discharged, with 72.5% diagnosed with EOS and 89% with LOS. There was a significant difference in gastric aspirate cytology when associated with expiry and discharge. Out of 167 neonates, 13.77% were culture-positive for neonatal sepsis. Out of 23 organisms, 82.6% were resistant, while, 17.4% were not. Staph aureus was the major causative organisms. Among the Gram Positive and Negative bacteria, the highest sensitivity was observed for imipenum. All gram-positive bacteria were resistant to cotrimazole, tobramycin, and erythromycin. Conclusions: Implementation of effective preventive strategies to combat the emergence of antibiotic resistance is urgently needed.